(untitled) (Ameghiniana, 2017)
A new record of fossil moss in Miocene amber from Chiapas, southern Mexico, is hereby presented. The fossil moss is assigned to the genus Hypnodontopsis Iwatsuki et Noguchi (Family Rhachitheciaceae) and characterized primarily by narrowly lanceolate to linear leaves arranged in rosettes, with erect costae, and short apiculate leaf tips, with upper cells larger than the lower cells. This sample, for which current worldwide distribution consists of at least three disjunct and geographically restricted occurrences, represents the first fossil record of the genus Hypnodontopsis in the Americas. While Hypnodontopsis is represented by five fossil species known from Eocene Baltic and Saxon amber, extant species are known from Asia, Africa and Mexico. The new fossil specimen most closely resembles the extant species Hypnodontopsis mexicana (Thér.) H. Robins, synonymous with the fossil species Hypnodontopsis conferta (Goeppert and Berendt) J.-P. Frahm. from Eocene Baltic amber. Hypnodontopsis mexicana can only be found in central Mexico (America) and in Uganda (Africa). Accordingly, the distribution of current and extinct species of Hypnodontopsis suggests that the genus diversified in both Laurasia and Gondwana and then suffered extinction by the end of the Paleogene in Europe. Resumen. PRIMER REGISTRO FÓSIL DE HYPNODONTOPSIS (BRYOPSIDA: RHACHITHECIACEAE) DEL CONTINENTE AMERICANO. Se presenta un nuevo registro de musgo fósil en ámbar miocénico de Chiapas, al sur de México. El musgo fósil está asignado al género Hypnodontopsis Iwatsuki et Noguchi (Familia Rhachitheciaceae). El ejemplar se caracteriza por presentar hojas estrechamente lanceoladas a lineares y dispuestas en rosetas, con costas erectas, y con ápices agudos, con células superiores más gruesas que las células inferiores. Este representa el primer registro fósil del género Hypnodontopsis para América, cuya distribución actual consiste en al menos tres ocurrencias separadas y geográficamente restringidas. Hypnodontopsis está representado por cinco especies fósiles de ámbar del Eoceno del Báltico y Sajonia, mientras que las especies actuales se encuentran en Asia, África y México. El nuevo espécimen fósil se asemeja a la especie actual Hypnodontopsis mexicana (Ther.) H. Robins., sinónimo de la especie fósil Hypnodontopsis conferta (Goeppert y Berendt) J.-P. Frahm. en el ámbar del Eoceno del Báltico. Hypnodontopsis mexicana sólo se encuentra en el Centro de México (América) y en Uganda (África). De acuerdo a lo anterior, la distribución de las especies actuales y extintas de Hypnodontopsis sugiere que el género se diversificó tanto en Laurasia como en Gondwana, seguido de una extinción, en Europa, al final del Paleógeno.